L'autonomie de l'enfant en question - Jean-Claude Quentel (Nantes Université, 2014)
A reflection on the autonomy of the child can only be developed in the context of a discussion of the status one accords the child. Even if one understands this status in terms of its social dimension, and more particularly in terms of its political dimension (in the etymological sense of being a citizen), one cannot reduce the status of the child to that dimension. The status of the child also raises an anthropological question concerning the specificity of the functioning of the child - something which is often denied today. No doubt the exercise of autonomy is an issue but we need to ask whether autonomy itself and the processes which it presupposes can be simply conferred or decreed. How answer that question in terms of the status of the child and the specificity of its functioning ?